Advancing Exposure Assessment of PM2.5 Using Satellite Remote Sensing: A Review - Hyung Joo Lee (Asian Journal of Atmospheric Environment, 2020)
Epidemiological studies have reported the associations of adverse health outcomes with ambient particulate matter with aerodynamic diameter ≤2.5 μm (PM2.5). While these studies have accumulated increasingly refined evidence on PM2.5-health associations, the needs for more advanced PM2.5 exposure models have also grown. For the last two decades, PM2.5 estimation approaches using satellite remote sensing have been developed and advanced, taking advantage of quantitative aerosol data (e.g., aerosol optical depth; AOD), the development of satellite instruments and data retrieval algorithms, and the application of statistical and machine learning techniques. Subsequently, the satellite-based PM2.5 concentrations have contributed to health effect studies by providing spatially resolved exposure estimates of ambient PM2.5 and thus reducing exposure misclassification. This article summarizes previous development and recent advancement of satellite-based PM2.5 exposure assessment in the context of satellite aerosol products and PM2.5 estimation methodologies. Furthermore, this article deals with enhanced satellite capabilities of generating the exposure estimates of PM2.5 composition and time-resolved PM2.5. Finally, the future directions of satellite-based exposure assessment are discussed based on research needs and the satellite remote sensing technology of addressing them.